A scenario study of the acceptability to ocean users of more and less invasive management after shark-human interactions. (July 2021) - Simmons, Peter; Mehmet, Michael; Curley, Belinda; Ivory, Nicola; Callaghan, Kane; Wolfenden, Kim; Xie, Gang
Abstract: Little is known about relationships between features of shark-human interactions and community expectations of authorities to respond. Previous research reports attitudes to wildlife management are influenced by context. This study comprised three phases. Phase one analysed social media related to shark management, identifying five commonly discussed variables in shark-human interaction contexts likely to influence attitudes towards management response. These context variables were: Level of human use of location; recency of other bites at the location; activity of victim; time of day; severity of harm to victim. Phase two used focus groups with ocean users to validate the Phase one context variables, and refine scenarios and management response options for Phase three, an experimental survey measuring the influence of context variables on New South Wales ocean user attitudes to management responses. The article focuses on Phase three, which randomly assigned participants ( N = 1769) one of 48 shark-human interaction scenarios comprising different manipulations of the five context variables. Participants rated support for 20 shark management response options. Contrary to expectations, context variables did not influence attitudes to shark management responses. There was almost unanimous support for education and research as preferred response to managing risk from sharks, and little support for invasive strategies perceived to harm marine life, such as shark nets and drumlines. Support for shark management responses decreased as invasiveness of the response increased. The findings reflect community dislike of 'knee-jerk' policy making, indicating that attitudes to shark management are relatively stable, and do not fluctuate in response to specific incidents. Highlights: Features of the context of human-shark interactions did not influence preferences for shark management responses. Attitudes to shark management response are relatively stable, not fluctuating in response to specific incidents. Non-invasive information and drone surveillance are supported as first response. The more invasive the management response, the lower the level of support.